Motion control of multiple autonomous ships to approach a target without being detected. (6th March 2018) - Kim, Jonghoek; Kim, Sanghoek
We introduce a motion control which is a stealth strategy of a team of autonomous ships to approach a target without being detected. The target is equipped with a radar to detect a nearby ship. In the team, one ship, the leader, has a stealth ability not to be detected by a radar as it approaches the target. We steer the leader so that it moves to the target while appearing to be at the same bearing line from the target to the leader. Assuming that the target can readily observe optical flow, but only poorly sense looming, this type of motion by the leader is difficult to be detected by the target. We steer every ship, except for the leader, so that a pulse signal emitted from the radar on the target cannot reach any ship, since the signal is blocked by the leader. In this way, even in the case where multiple ships approach the target, the target cannot detect any ship. In our control law, a ship, except for the leader, does not have to access the position of the target in real time. However, a ship must access the bearing line from the target to the leader in real time. Our motion control is inspired by line-of-sight guidance control laws and is developed in discrete-time systems. We present MATLAB simulations to verify the performance of our motion control law.